Fanvids: Television, Women, and Home Media Re-use, by E. Charlotte Stevens [book review] - Lauren Watson (Transformative Works and Cultures, 2022)
Review of E. Charlotte Stevens, Fanvids: Television, women, and home media re-use. Amsterdam: Amsterdam University Press, 2020, hardcover, €113 (278p), ISBN 978-9462985865.